Evidence for cytomegalovirus-induced haemophagocytic syndrome in a young patient with AIDS. (25th September 2013) - Ohkuma, Kosuke; Saraya, Takeshi; Sada, Mitsuru; Kawai, Shin
Abstract : A 29-year-old man with HIV infection was referred to our department because of a 1-month history of low-grade fever and fatigue. Bone marrow aspiration and biopsy showed findings consistent with haemophagocytic syndrome (HPS), and immunohistochemical assessment showed cytomegalovirus (CMV) infection. HIV-associated HPS can occur at any stages of HIV disease and requires diverse differential diagnosis. CMV-associated HPS (CMV-HPS) in patients with HIV infection is relatively rare, but the present case showed that the clinicians should consider the possibility of CMV-HPS as a clinical feature of CMV infection.